The Value of the Case for the Applicant: A Criterion for the Differentiation of Case Proceedings or of Access to Justice? - Korol, Denys (Teisė, 2020)
For the first time in Ukraine, the institute of small claims procedure has been introduced in the updated civil procedural legislation. The differentiation of cases, which can be considered in simplified or general proceedings, is carried out not only on the basis of the size of the claim, but on the basis of a number of criteria, for instance, the value of the case for the applicant, assessment of which is the main aim of this paper.